Hampea lanceolata (Malvaceae, Malvoideae), a new species from Chiapas and Oaxaca, Mexico - Areces-Berazain, Fabiola; Vega-Lopez, Victor J. (Phytotaxa, 2019)
Hampea lanceolata is described from the highlands of northern Chiapas and the Chimalapas region of Oaxaca, Mexico.This species had been confused with Hampea longipes, although it is most closely allied to Hampea montebellensis. It differs from H. longipes by the coarse brown pubescence, the relatively narrower leaves with domatia at the junction of main veins, the longer bracteoles, and the smaller fruits with one seed per locule. From H. montebellensis, it differs in having glabrous leaves with domatia, relatively longer pedicels, and in the glabrous or very sparsely puberulent inner fruit walls.